Wettability of laser surface modified soda lime silica glass - Abdul Fattah, Mohamad Tahir; Nur Najwa, Khairul Azman; Syarifah Nur Aqida, Syed Ahmad; Izwan, Ismail (Penerbit Akademia Baru, 2025)
Transformation of hydrophilic Soda Lime Glass (SLS) into hydrophobic glass without using any chemical processing has been a major setback in surface modification. This paper studies the effect of laser processing parameters in transforming the glass wettability using a 50 W fibre laser with a variation in hatch spacing, hatch style, scanning speed and frequency. A Design of Experiment (DOE) methodology was applied with a total of 28 runs to evaluate the water contact angle using the sessile drop method. Analysis of Variance (ANOVA) was performed to study each factor’s contribution to the response. The result shows that hatching style and spacing are the most crucial factors in determining the water contact angle, followed by speed and frequency. It is found that hatch spacing and style contributed approximately 28% and 9%, respectively, to the contact angle and wettability transformation. Negative interaction between hatch spacing and water contact angle concluded this study with cross-hatch is better than line hatch. Meanwhile, cross-type hatch produced better outcomes on contact angle than line hatch. The findings are significant to designing self-cleaning glass surfaces for applications like solar panels and high-rise building glass windows.